Evolution of New Functions De Novo and from Preexisting Genes - Andersson, Dan I. (Cold Spring Harb Perspect Biol, 2015)
How the enormous structural and functional diversity of new genes and proteins was generated (estimated to be 10(10)–10(12) different proteins in all organisms on earth [Choi I-G, Kim S-H. 2006. Evolution of protein structural classes and protein sequence families. Proc Natl Acad Sci 103: 14056–14061] is a central biological question that has a long and rich history. Extensive work during the last 80 years have shown that new genes that play important roles in lineage-specific phenotypes and adaptation can originate through a multitude of different mechanisms, including duplication, lateral gene transfer, gene fusion/fission, and de novo origination. In this review, we focus on two main processes as generators of new functions: evolution of new genes by duplication and divergence of pre-existing genes and de novo gene origination in which a whole protein-coding gene evolves from a noncoding sequence.